2023
DOI: 10.3390/ma16072734
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Silicate-Based Sealer Dentinal Tubule Penetration—A Systematic Review of In Vitro Studies

Abstract: The aim of this systematic review was to perform a qualitative synthesis of in vitro studies which evaluate and compare the penetration of calcium silicate-based sealers into dentinal tubules. A systematic advanced search was performed in Scopus, Embase, Medline (via PubMed), Web of Science, and Cochrane databases on the 1 December 2022. In vitro studies that compared the tubular penetration of at least two calcium silicate-based sealers in extracted human teeth were eligible. PRILE 2021 guidelines were used f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 96 publications
1
3
0
Order By: Relevance
“…Consistent with prior studies, we observed a substantial reduction in PAI scores following endodontic treatment in both groups [56,57]. In line with other investigations, tooth mobility and pain at the intervention site were significantly reduced after treatment across both sealers [58,59].…”
Section: Analysis Of Results and Literature Findingssupporting
confidence: 92%
“…Consistent with prior studies, we observed a substantial reduction in PAI scores following endodontic treatment in both groups [56,57]. In line with other investigations, tooth mobility and pain at the intervention site were significantly reduced after treatment across both sealers [58,59].…”
Section: Analysis Of Results and Literature Findingssupporting
confidence: 92%
“…The sealer adaptation depends on many factors, including smear layer removal, root canal dimension, dentin permeability, dentinal tubule diameter, physical and chemical properties, constituents, particle size, consistency, surface tension, and contact angle of the root canal sealers. 21 - 23 …”
Section: Discussionmentioning
confidence: 99%
“…Similarly, other findings have confirmed that using small particles decreases the contact angle and increases the surface area of the sealer, thereby enhancing the spread and adaptation of the sealer into lateral and accessory root canals. 22 , 23 Therefore, the small particle size and greater fluidity of the C 3 S-BG-P and Nishika allowed their better adaptation to root canal walls. Chew et al 30 compared three different sealers (EndoSeal MTA, CeraSeal, and Nishika Canal Sealer BG) with an AH Plus in oval root canals.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, rhodamine has less affinity to calcium in the sealer. For this reason, Fluo-3 dye was suggested as a suitable dye alternative to rhodamine in the detection of the sealer penetration of calciumsilicate-based endodontic sealers (Ashkar et al, 2023;Coronas et al, 2020). Fluo-3 dye can bind to the calcium in these sealers and cause fluorescence.…”
Section: Mean Penetration Depthmentioning
confidence: 99%